IS THERE A SIGNIFICANT IMPACT ON THE BANK PERFORMANCS DURING AND BEFORE COVID 19 - Idialis, Alifah Rokhmah; Angelita, Reka; Achmadi, Kholikul; Rahmawati, Sheila; Baiduri, Intan (Proceedings of the International Conference of Islamic Economics and Business (ICONIES), 2024)
The Covid-19 pandemic has led to a decline in financial performance in Indonesia. The weakening of  a country's economy has an impact on the banking sector because of the function of banks as financial intermediary institutions. This study aims to analyze and identify the impact of COVID-19 on the financial performance of 47 banks listed on the Indonesian stock exchange, both conventional commercial banks and Islamic banks. Bank financial performance in this study, namely Capital (CAR), Assets (NPL), Profitability (NIM, ROE, ROA, & BOPO) and Liquidity (LOR). Using panel data with grouping before covid-19 (2017-2019) and during covid -19 (2020-2022). Included in non-parametric research using the Wilcoxon Signed Rank Test. The test results showed that there were significant differences between before and during Covid-19 for several financial performance variables including the Capital Adequacy Ratio (CAR), Net Interest Margin (NIM), Return On Assets (ROA), and Loan to Deposit Ratio (LOR) with a prob value of z statistics less than significance level of 5% and 10%. While Non Performing Loans (NPL), Return On Equity (ROE), and Operating Expenses to Operating Income (BOPO) with a prob value of z statistics greater than significance levl at 5% and 10%, which can be concluded that there is no significant difference between before and during Covid-19. From the result can conclude Covid-19 has a negative impact on several banking financial performance indicators especially on the performance of banks with indicators Capital Adequacy Ratio (CAR), Net Interest Margin (NIM), Return On Assets (ROA), and Loan to Deposit Ratio (LOR). In other words, covid-19 has had a considerable and significant impact on capital performance, capital performance (CAR), profitability performance (NIM and ROA), and liquidity performance (LOR). Covid-19 has significantly impacted the increase in Capital Adequacy Ratio (CAR). Covid-19 had a significant impact on the decrease in Net Interest Margin (NIM). Covid-19 has had a significant impact on the decline in Return on assets (ROA). The last covid-19 had a significant impact on the decline Loan to Deposit Ratio (LOR).